Looking in the Honest Mirror of Privilege: “Polite White” Reflections - McDonald, Janis L. (Columbia Journal of Gender and Law, 2003)
When I look in the honest mirror of white feminist legal scholarship I see reflected back at me a failure by those of us “polite white” feminists to seriously address the substantive critiques authored by women of color in the last twenty years. It is time to develop an agenda that does more than cite to the work of these important critiques. It is time to follow their lead and work to transform our own thinking to confront personal privilege that may shape our approaches to scholarship. At the final panel of the Conference, “Why a Feminist Law Journal?”, which is the subject of this symposium, one of the professors present made a statement that went unaddressed. The bold, honest observation made by Professor Taunya Lovell Banks continues to concern me, particularly because no one really responded. She referred to the many Black, Latina, and Asian women who have pointed out that white legal feminist scholars have not broadened the inquiry to challenge the essentialist assumptions inherent in their focus. Professor Banks added that “nothing I have heard here today makes me feel any differently about this failure.” I prepared myself for the intense discussion that would follow. As someone who works to uncover my own white privilege I waited a moment to listen to how others would respond to her very frank comment. I appreciated her honesty and wanted to engage in examining our own actions to figure out what should be done to further the dialogue about this problem. I wanted to figure out how to make those concerns a part of my responsibility as a critical race feminist. I am learning to take my part in admitting the limits of my own evolving perspective as a critical white feminist legal scholar.